Due Professional Care, Kompleksitas Tugas, Ukuran Kantor Akuntan Publik, dan Kualitas Audit pada Kantor Akuntan Publik Medan - Gilbert, Gilbert; Monica, Georgina Cynthia; Fransisca, Yoana; Sitepu, Wilsa Road Betterment (E-Jurnal Akuntansi; Vol 30 No 12 (2020), 2020)
Auditor have several internal and external factors that affect audit quality. The practice that are guided by the norm and principle of the public accountant profession that are related and independent are audit quality. An auditor must have a high professionalism spirit so that there are no error in the audit process. The purpose of this research is to analyze how big the relationship between due professional care on audit quality and whether the audit quality can be affected by the complexity of the duties and size of PAF.This research method is purposive sampling method, the data is obtained through questionnaire distributed to auditors of public accountants in Medan. Evidence obtained from the research results is Due Professional Care and Task Complexity has a significant influence on Audit Quality. Meanwhile, PAF Size doesn’t have a significant effect on Audit Quality . Keywords: Due Professional Care; Task Complexity; PAF Size; Audit Quality.